Impact of Rock Mass Strength Anisotropy with Depth on Slope Stability Under Excavation Disturbance - Gulseren Dagdelenler (Applied Sciences)
In open-pit excavations, overburden rock mass is disturbed by processes like blasting and mechanical excavation, leading to a reduction in mechanical properties. Accounting for this disturbance is essential for ensuring slope stability, optimizing costs, and maintaining feasibility. The Hoek–Brown failure criterion, a widely used empirical method in rock mechanics, incorporates the disturbance factor to reflect the reduction in rock mass strength after disturbance. This study reviews five approaches from the literature regarding the role of disturbance in rock mechanics, focusing on its impact on the factor of safety and the volume of rock mass above the potential failure surface. Additionally, an “S” shaped decay formulation was proposed as an alternative to existing equations. A key consideration is the transitional disturbance effect, which reflects the gradual change from a fully disturbed rock mass near the excavation surface to an undisturbed rock mass with increasing depth. Among the examined approaches, the “S” shaped decay equation, informed by insights from previous studies, appears to be the most realistic. One approach assumes the disturbance factor is highest at the surface due to the removal of blasted rock, leading to a fully disturbed rock mass in front of the excavation face. The disturbance then decreases with depth, transitioning to an undisturbed condition depending on the excavation method. Even when the rock mass is homogeneous and isotropic in joint properties, excavation induces anisotropy in mass strength, causing overall strength to increase with depth. This study also investigates the effect of anisotropic strength behavior resulting from the disturbance factor. For incorporating transitional disturbance in the design stage, both circular and combined failure mechanisms should be considered for a comprehensive understanding of slope stability.